2010
DOI: 10.1002/cncr.25087
|View full text |Cite
|
Sign up to set email alerts
|

Trends in oropharyngeal and oral cavity cancer incidence of human papillomavirus (HPV)‐related and HPV‐unrelated sites in a multicultural population

Abstract: BACKGROUND:There is a growing recognition of the involvement of human papilloma virus infection in the etiology of head and neck cancers at some sites, mainly the base of the tongue, tonsils, and other oropharynx (hereafter termed oropharyngeal cancer). Other oral sites (hereafter termed oral cavity cancer [OCC]) show a stronger association with tobacco and alcohol. Little is known about the ethnic variation in incidence for these cancers. This study determined incidence rates of OCC and oropharyngeal cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
148
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 27 publications
8
148
1
6
Order By: Relevance
“…16 A recent study from British Columbia mirrors the overall Canadian trends. 17 We observed that the increase in incidence of oropharyngeal cancer among men was twice that among women (annual percentage change 3.4 v. 1.5) between 1975 and 2009. Similarly, both Canadian 16 and US 18 data show that the increased incidence of HPV-associated head and neck cancers was greater among men, most notably the younger groups.…”
Section: Cmaj Openmentioning
confidence: 74%
See 1 more Smart Citation
“…16 A recent study from British Columbia mirrors the overall Canadian trends. 17 We observed that the increase in incidence of oropharyngeal cancer among men was twice that among women (annual percentage change 3.4 v. 1.5) between 1975 and 2009. Similarly, both Canadian 16 and US 18 data show that the increased incidence of HPV-associated head and neck cancers was greater among men, most notably the younger groups.…”
Section: Cmaj Openmentioning
confidence: 74%
“…Similarly, both Canadian 16 and US 18 data show that the increased incidence of HPV-associated head and neck cancers was greater among men, most notably the younger groups. In 2 previously reported Canadian studies, 16,17 ethnic minorities appeared to be at higher risk than the general population of both oropharyngeal cancer and oral cavity cancers. In the US, non-Hispanic white and Hispanic populations experienced greater increases in the incidence of HPV-associated head and neck cancers than other groups.…”
Section: Cmaj Openmentioning
confidence: 80%
“…In the United States and Europe, there is compelling evidence that opc is on the rise, and that the increase is primarily a result of increasing rates of In Canada, population-based studies have provided indirect evidence of the phenomenon by demonstrating that the incidence of head-and-neck cancers at hpv-related anatomic sites (oropharynx) are rising and that those of smoking-related sites (for example, oral cavity) are declining 2,11,12 . However, no previous study has performed hpv testing of tumour samples, and thus we have attempted to provide the first direct evidence of this dramatic shift in disease prevalence and demographics.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, studies have shown that OSCC and OPSCC have different incidence rate trends, etiology, and survival outcome [1]. For instance, human papillomavirus (HPV) is known as an important etiology for OPSCC, especially tonsil cancer.…”
Section: Introductionmentioning
confidence: 99%